12th International Conference on Thalassemia and the Haemoglobinopathies, 11-14 May 2011, Antalya, Turkey - Guest Editors: Aurelio Maggio, Duran Canatan, Androulla Eleftheriou (Thalassemia Reports, 2011)
This abstract book contains all abstracts presented to the 12th International Conference on Thalassaemia and Other Haemoglobinopathies, and the 14th TIF Conference for Patients and Parents, 11-14 May 2011, Antalya, Turkey.